2011
DOI: 10.5812/kowsar.1735143x.781
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Two Common HFE Gene Mutations (C282Y and H63D) in a group of Iranian Patients with Cryptogenic Cirrhosis

Abstract: BackgroundThe human HFE gene (a key component of iron homeostasis in humans) is involved in hereditary hemochromatosis, a common autosomal recessive genetic disorder that is characterized by excessive intestinal iron absorption and progressive iron overload.ObjectivesIn this study, we assessed the frequency of two common forms of hemochromatosis HFE gene mutation (C282Y and H63D) in patients suffering from cryptogenic cirrhosis.Patients and MethodsOne hundred and fifty individuals were included in this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…In addition, conflicting data on the correlation between overall liver cirrhosis and HFE gene mutations were observed. For instance, the polymorphisms of the HFE gene are not essential for cryptogenic cirrhosis in the southern Iranian population [ 50 ]. C282Y might be linked to the risk of HCC in patients with alcoholic-related cirrhosis [ 24 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, conflicting data on the correlation between overall liver cirrhosis and HFE gene mutations were observed. For instance, the polymorphisms of the HFE gene are not essential for cryptogenic cirrhosis in the southern Iranian population [ 50 ]. C282Y might be linked to the risk of HCC in patients with alcoholic-related cirrhosis [ 24 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their HH patients were from the southern part of Iran, whereas our cases were mostly from the north; and this difference may account for the varied findings of these 2 studies. Recently, another report from southern Iran by Jowkar et al [34] showed no cases of either a homozygous or heterozygous C282Y mutation; however, heterozygosity of H63D mutation was detected in 22% of patients with cryptogenic cirrhosis and in 28% of the normal population. Either our study or Yavarian’s [11] or Jowkar’s [34] are not representative of different Iranian ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another report from southern Iran by Jowkar et al [34] showed no cases of either a homozygous or heterozygous C282Y mutation; however, heterozygosity of H63D mutation was detected in 22% of patients with cryptogenic cirrhosis and in 28% of the normal population. Either our study or Yavarian’s [11] or Jowkar’s [34] are not representative of different Iranian ethnic groups. As mentioned, their samples mostly came from the south of the country, while ours were generally referred from the northern parts of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The patients' reluctance to admit to alcohol consumption along with the absence of advanced molecular techniques result in a higher number of false positive cases of cryptogenic cirrhosis in Iran. It is also not quite plausible to conclude that "HH is not a major cause of cryptogenic cirrhosis in the Iranian population" as Jowkar et al have indicated in their study [2]. Perhaps, the authors meant to say that the development of cirrhosis in these patients cannot be attributed to HFE mutations.…”
mentioning
confidence: 89%
“…In a study by Jowkar et al [2] published in the November issue of Hepatitis Monthly, the C282Y mutation was not detected in cryptogenic cirrhosis patients as well as healthy individuals; however, 22% of the patients and 28% of the healthy individuals were found to be heterozygous for the H63D mutation. Therefore, they concluded that HH is not the major cause of cryptogenic cirrhosis in the Iranian population.…”
mentioning
confidence: 99%